Prevalence of peripheral artery disease in diabetes mellitus: research article - Tyagi, Vinod; Gupta, Abhishek; Bansal, Naman; Virmani, S. K. (International Journal of Research in Medical Sciences, 2017)
Background: Peripheral artery disease is a major macrovascular complication of diabetes mellitus. Patients with diabetes mellitus have an increased prevalence of PAD. The ankle brachial pressure index is an easy, non invasive and often under utilised tool for diagnosis of PAD. Methods: In the present study, 100 patients from Western Uttar Pradesh with diabetes mellitus were enrolled to find out prevalence of peripheral vascular disease using ankle brachial pressure index and study the associated risk factors. Results: 59 percent of the subjects were female and 41 percent were male. Ankle-brachial index (ABI) examination of patients indicated Abnormal (ABI= <0.9), in 40 cases. Conclusions: it can be concluded that peripheral vascular disease in Diabetes Mellitus is more commonly associated than is generally believed.